DEVELOPMENT OF A GUIDEBOOK FOR SEKOLAH PLUS NGAJI (SPN) IN STATE ELEMENTARY SCHOOLS IN NGANTANG DISTRICT - Melia Fitriani; Endang Poerwanti; Nurul Zuriah; Agus Tinus (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
This study provides an overview of the development of a guidebook for Sekolah Plus Ngaji (SPN) program in State Elementary Schools in Ngantang District. The objectives of this study are: (1) Describe the development of a guidebook for the SPN program, (2) Describe the applicability of the SPN guidebook. This research is a development research with the ADDIE model. The research instrument is a non-test instrument in the form of a structured questionnaire. SPN Guidebook is very important because the implementation of this program is new. It is an implementation of the Gemma program (Gerakan Malang Mengaji). In its implementation, SPN requires a guidebook that can be used by teachers as a guideline for implementing activities. In accordance with the analysis of teacher and student needs, the guidebook created covers all programs in SPN, namely Reading and Writing the Al-Quran (BTQ), congregational Dhuha prayer, Dhuhur prayer, habituation of Asmaul Husna and character. The results of expert validation and user responses show that the SPN digital guidebook can be used well. The response to the applicability of the guidebook reached 92.9%. This study shows the importance of this guidebook in activities at school.